2019
DOI: 10.14581/jer.19007
|View full text |Cite
|
Sign up to set email alerts
|

Parental Knoweldge, Attitude, and Perception about Epilepsy and Sociocultural Barriers to Treatment

Abstract: The present study focused on assessing parental knowledge, attitudes, and perceptions about epilepsy as well as addressing the socio-cultural barriers to its treatment. Methods: Data were collected from outpatient consultations in the neurology department of a tertiary referral center in South India. Parents of sixty children suffering from epilepsy in the age-group of 4-15 years were interviewed to explore their knowledge, attitudes, and perceptions about epilepsy. They were recruited in 2015 over a consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(46 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…This could be attributed to the prevailing low socio-economic level in the study sample, which would increase the caregivers' negative feelings towards epilepsy, considering it a shame or stigma that needs to be hidden, in addition to other related misconceptions. The findings are in agreement with Rani and Thomas [38] whose study in India revealed negative parents' attitudes towards their epilepsy that affected their children, attributing it to evil spirits and thus tending to use religious and spiritual approaches to treatment.…”
Section: Self-efficacy Of Caregivers Of Children With Epilepsy Shahinsupporting
confidence: 90%
“…This could be attributed to the prevailing low socio-economic level in the study sample, which would increase the caregivers' negative feelings towards epilepsy, considering it a shame or stigma that needs to be hidden, in addition to other related misconceptions. The findings are in agreement with Rani and Thomas [38] whose study in India revealed negative parents' attitudes towards their epilepsy that affected their children, attributing it to evil spirits and thus tending to use religious and spiritual approaches to treatment.…”
Section: Self-efficacy Of Caregivers Of Children With Epilepsy Shahinsupporting
confidence: 90%
“…14 The FMF severity score comprised of age at FMF onset, frequency of attacks, presence of arthritis, erysipelas-like erythema, amyloidosis, and the required dose of colchicine prophylaxis necessary to control FMF symptoms. Escalating scores indicate mild (score, 1-5), moderate (score, [6][7][8][9], and severe (score, >10) FMF activity. 15 Three self-administered surveys which were developed by authors, were given to caregivers: a. Caregivers' socio-demographics form:…”
Section: Methodsmentioning
confidence: 99%
“…Parental knowledge about chronic diseases, such as rheumatic diseases, epilepsy, thalassemia, neurofibromatosis, and hypospadias, has been investigated previously. [6][7][8][9][10][11] However, to date, no data has been reported about the parental knowledge of pediatric patients with FMF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because cultural barriers may influence and delay an individual's care-seeking behavior, these barriers deserve consideration when examining and intervening to mitigate these results, and would motivate qualitative and mixed-methods work. [19][20][21][22] It is important to note, however, that in this study we collapsed a number of racial and ethnic groups due to small sample sizes, and therefore caution should be taken in assuming a homogenous effect across these groups. These cultural factors likely vary, and understanding the nuance between these groups is an important direction for future research.…”
Section: Author Manuscript Author Manuscript Author Manuscript Author Manuscriptmentioning
confidence: 99%